Publishing & the Book in Africa: A Literature Review for 2015. - Zell, Hans (My University, 2019)
This is a review of select new literature in English that has appeared on the topic of publishing and book development in Africa published during the course of 2015. It covers books, papers in edited collections, journal articles, Internet documents and reports, interviews, as well as a number of blog postings (with their posting dates indicated.) Newspaper articles are not included in this literature review, nor are video presentations. Records are grouped under a range of regional/country and topic-specific headings. It should be noted that, for the most part, literature on particular topics, e.g. children’s book publishing, copyright, digital publishing, reading culture and reading promotion, etc. is listed under topic/subject rather than country headings. Most journal articles published online are freely accessible unless otherwise indicated. All these records, and many more, will shortly be integrated into the online database of Publishing, Books & Reading in Sub-Saharan Africa http://www.hanszell.co.uk/cgibin/online/pbrssa.shtml, which is currently in the process of migrating to a new hosting institution in Nigeria (see press release at http://www.hanszell.co.uk/Press%20release.pdf), from where it will shortly be re-launched on a more dynamic digital platform, and become freely available as Drupal-based open access/open source content management platform. It is expected that the new database will be launched early in 2016, when the first batch of updates and new records will then be posted.
Keywords: Africa; African studies; Bibliography; Publishing and book industries; Reference; Scholarly publishing